The Use of a Narrow Implant with Edentulous Patients: A Systematic Review - Sultan A. Alqahtani; Sulaiman A Alshammari (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Implant selection has been highly emphasized in fully edentulous patients, where using slender diameter implants has become a central area of interest in dental implantology, mainly where patients have limited bone width and height. New developments in implant technology have demonstrated that these implants are as effective as broader implants and may be used for tooth replacement. Objectives: This systematically planned and executed article aims to discuss the difficulties involving complications in completely edentulous patients along with the success and failure rates of narrow diameter implants. Methods: Electronic databases, including but not limited to MEDLINE and Google Scholar, were searched for articles with standard protocol as per the “PRISMA guidelines”. The criteria for paper selection involved articles between 2020 and 2024, limited to peer-reviewed sources that dealt with the use of implants with lesser diameter in edentulous individuals. Nine papers were chosen from the initial search’s 2035 results based on specific inclusion criteria. Results: The analysis shows a high overall long-term success rate of small-diameter implants (SDIs), ranging from 94.6% to 100%, with minimal marginal bone loss. Studies report cumulative survival rates such as 99.4% at a two-year follow-up and 97.7% over 55 months. Marginal bone loss was low, with some studies showing mean values of 0.15 mm after 24 months and 0.14 ± 0.39 mm following functional loading over 1–4 years. Additionally, patient satisfaction was high, with some studies reporting that 99% of patients maintained good soft tissue health, and prosthetic survival rates reached 100%. The literature confirms that narrow implants are a viable solution for ridge resorption and for use in medically compromised patients. Conclusion: With much higher survival rates than conventional, large implants, small-diameter implants are a good and safe option for edentulous patients undergoing prosthetic rehabilitation. This review adds knowledge to the current debate about the appropriate approaches to dental implantology, discussing how thin implants can be used in treatment and possible drawbacks.